Influence of specific tobacco endophytic Bacillus on tobacco leaf quality enhancement during fermentation - Wei, Jinbin; Song, Kai; Zang, Zhipeng; Yang, Hongjing; Gao, Yuzhen; Zhang, Jiandong; Wang, Zhen; Liu, Chen (Frontiers in Microbiology, 2024)
IntroductionThis study aimed to investigate the potential role of endophytic bacteria in tobacco leaves during the fermentation process to enhance the quality of tobacco.MethodsWe isolated 11 endophytic bacteria from fresh tobacco leaves and selected Bacillus halotolerans NS36 and Bacillus mycoides NS75 based on sensory evaluation, both of which significantly improved the sensory quality of tobacco leaves.ResultsSpecifically, NS36 decreased offensive taste in tobacco leaves, while NS75 improved the quality by increasing the aroma. Chemical analysis revealed that fermentation with B. halotolerans NS36 significantly decreased the content of irritant compounds such as lignin, cellulose, starch, and pectin. In contrast, fermentation with B. mycoides NS75 reduced the content of cellulose, starch, and protein, while significantly increasing the content of Amadori compounds and glycosides. Through whole-genome sequencing, we predicted enzyme systems related to these chemical changes. B. halotolerans NS36 mainly secreted enzyme systems associated with the degradation of lignin, cellulose, starch, and pectin, thereby reducing irritants in tobacco leaves, diminishing unpleasant tastes, and achieving a more balanced sensory quality. B. mycoides NS75, on the other hand, secreted enzyme systems related to protein and glycoside hydrolysis, increasing Maillard reaction products and glycosylated compounds in tobacco leaves, thus enhancing the aroma quality and quantity.DiscussionThe findings of this study offer a new perspective for the tobacco industry, namely, the use of endophytic bacilli to improve the off-flavors and aroma of tobacco leaves, which could not only enhance the industrial applicability of tobacco leaves but also potentially strengthen the market competitiveness of products. These discoveries lay the foundation for further research and application, especially in the development of new biotechnologies to improve the quality of tobacco products.